Effect of thermal insulation of the back side of PV modules on the module temperature. (3rd May 2016) - Koehl, Michael; Hamperl, Simon; Heck, Markus
Abstract: The module temperatures of free‐standing modules were compared with identical modules with thermally insulated back side simulating roof integration for 45° south orientation in Freiburg, Germany, at 1000 W/m 2 solar irradiation. The thickness of the thermal insulation was varied in order to find a minimum thickness sufficient for suppressing the heat losses and for the simulation of roof integration. The module‐dependent coefficients for the Faiman model for the module temperature depend on the back‐side heat losses. A correction for roof integration is proposed. This model allows the calculation of the maximum temperatures reached for given climatic situations (irradiation in plane of array, ambient temperature, and wind speed). Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Difference of the average photovoltaic module temperatures between non‐insulated references and with increasing insulation thickness for various module types exposed at 45° tilt to south in Freiburg, Germany, measured between 900 and 1100 W irradiance and normalized to 1000 W before averaging.